Partial Discharge and Dissolved Gas Analysis on 22kV MV Oil-type Transformer - Case Study - Inwanna, Woranan; Waiwicha, Supisara; Vanijkirati, Parada; Monkolsatitpong, Suriya; Chumpiboon, Komin; Pattanadech, Norasage (My University, 2024)
Detecting faults leading to potential failure of important power distributing transformers in the power system before an occurrence is an important attribute. Various inspection methods are available, however online PD and oil analysis remain the most preferred method. The methods mentioned do not require equipment shutdown. This paper introduces a case study of the 22kV transformer with online PD and DGA results indicating signs of problems in the insulation. The PD group found initially had an increase in density of signals during the three months and the magnitude shows an upward trend. DGA results found H2 and CH4 gas, the latter is a key gas indicating PD. Results show an increasing trend of almost three times as high during the latter half of the year. In addition, CO, CO2, and C2H6 gases were also found to be higher than average. Virtual inspection was conducted after the transformer was shut down. The surface is found to be uneven around the bus bar, causing high temperatures in the transformer which then impacts the insulation performance.
Keywords: DGA; dissolved gas; hot spot; partial discharge; transformer